Stereoselective Synthesis of Volicitin and 9-D1-Volicitin - Mamada, Shunki; Niwa, Kosuke; Toyoshima, Shoya; Seto, Yoshiya; Ogawa, Narihito (Synlett, 2024)
The synthesis of volicitin involved the condensation of l-(+)-glutamine with 17(S)-hydroxylinolenoic acid, derived from a Wittig reaction between the C10–C18 phosphonium salt and the C1–C9 aldehyde. The phosphonium salt was prepared through the alkynylation of a (Z)-allylic phosphate with an alkyne derived from (2S)-but-3-yn-2-ol. The deuterated aldehyde was derived with a 96% deuteration ratio by reduction of the C1–C9 methyl ester with NaBD4, followed by oxidation. Subsequently, 9-D1-volicitin was synthesized from the monodeuterated aldehyde by using the Wittig reaction and condensation with l-(+)-glutamine.
Keywords: volicitin; deuteration; alkynylation; Wittig reaction; condensation